U źródeł agresji. Eli Sagana psycho-antropologiczne spojrzenie na przemoc w kulturze - Sarnek, Marcin (Er(r)go. Teoria - Literatura - Kultura, 2003)
This essay offers an in-depth discussion of Eli Sagan's Cannibalism: Human Aggression and Cultural form.